Source-sink relations and effects of postanthesis canopy defoliation in wheat at low latitudes - Aggarwal, P.K.; Fischer, R.A.; Liboon, S.P. (Cambridge University Press, 1990)
Source–sink balance was studied by imposing different canopy defoliation treatments on wheat crops grown in Los Banos (Philippines) in 1985/86 and 1986/87, Sonora (Mexico) in 1972/73 and 1974/75 and New Delhi (India) in 1987/88. The crops were grown in replicated trials with optimum cultural management. Six defoliation treatments were imposed at anthesis on all shoots in the canopy in an area ranging between 1·65 and 3·0 m2. Defoliation reduced dry weight in proportion to the reduction in percentage light interception. The number of grains per unit land area was reduced slightly, and in most cases not significantly, except when all leaves were removed. Despite reduction of leaf lamina area index to as low as 0·5, the decrease in grain yield was small. In particular, flag leaf removal led to a remarkably small reduction in grain yield. Grain nitrogen content in defoliated crops decreased much less than expected from the amount of N removed by defoliation. The slope of the relation between reduction in grain yield with defoliation and reduction in post-anthesis dry matter accumulation was 0·56, indicating moderate source limitation for grain filling. The crops at the hottest site, in the Philippines, were less limited by source than the other crops. It is suggested that selection for smaller flag leaves may be worthwhile for high-input wheat crops.